Are there alternative methods to the evaluation of the functional repercussion of the pneumoconiosis in miners? An integrative review - Silva, Luan Nascimento; Coertjens, Marcelo; Costa, Tannara Patrícia Silva (Journal of Health Care, 2016)
Introduction: Although it is not used in a common way in workers with silicone and nor provided as a complementary test by the legislation, the 6-minute walk test (6MWT) has a low cost, clinical applicability and it evaluates signals and symptoms of cardiorespiratory and muscular systems. Objective: In this sense, the objective of this work was to analyze alternative methods to the traditional ones used to evaluate the functional repercussion of pneumoconiosis in miners. Materials and methods: It is a narrative review, done through research of the online databases of MedLine, SciELO and LILACS. The terms used were: occupational disease, pneumoconiosis, lung function, miners and exercise capacity. Results: We checked that there are limitations to detect abnormalities in the initial phase of the pneumoconiosis through the use of X-ray of the chest and spirometry. The CT scans are sensitive to measure the involvement progression, however they present a large financial cost. The 6MWT combines the low cost and sensibility in the evaluation of functional repercussions and exercise capacity during the pneumoconiosis.
Keywords: pneumoconiosis; occupational exposure; respiratory function test; physical fitness